Determinants of Entrepreneurial Intentions in ICT Industry: Gender and country of origin perspective - Pejić Bach, Mirjana; Merkač Skok, Marjana; Suša , Dalia (Naše gospodarstvo/Our economy, 2016)
Although many researchers agree that environmental and personal characteristics are important for becoming an entrepreneur, it is still not clear if their influence is equally significant. Numerous authors have pointed out unresolved matters regarding the relationship among innovativeness, gender, and entrepreneurial intensions. The aim of this paper is to explore the impact of gender and country of origin in relation to entrepreneurial intentions and innovative cognitive style. Research was conducted using a sample of students majoring in information and communication technologies from Croatia and Slovenia. The results revealed the influence of gender, country, attitudes toward entrepreneurship, and innovative cognitive style on entrepreneurial intentions.